Percepción de los enfermeros recién graduados sobre su autonomía profesional y sobre el proceso de la toma de decisiones del paciente - Berti, Heloisa Wey [UNESP]; Braga, Eliana Mara [UNESP]; De Godoy, Ilda [UNESP]; Spiri, Wilza Carla [UNESP]; Bocchi, Silvia Cristina Mangini [UNESP] (FapUNIFESP (SciELO), 2008)
This study involved newly graduated nurses performing in a public hospital and aimed at apprehending how they interpret the reality of their practice as well as their knowledge and experiences; at identifying and problematizing aspects related to the caregiving practice in terms of compliance with the autonomy bioethical framework and at pointing out ways to overcome the problems identified. The strategy adopted for data collection was the focal group and the theoretical framework was based on the Grounded Theory. Two phenomena emerged from the results: 1) Perceiving the fragility of nurse and patient autonomy and 2) Moving towards the strengthening of nurse and patient autonomy. This allowed for the identification of the core category: movement undertaken by newly graduated nurses towards the strengthening of their professional autonomy and towards patient autonomy. Understanding the experience enabled us to expand the knowledge concerning newly graduate nurses' coping, thus favoring our action as nursing professors.
Movement undertaken by newly graduated nurses towards the strengthening of their professional autonomy and towards patient autonomy
Keywords: Ethics; Hospital care; Nursing; Professional autonomy